A Pentamer Transcriptional Complex Including tal-1 and Retinoblastoma Protein Downmodulates c-kit Expression in Normal Erythroblasts - Vitelli, Luigi (American Society for Microbiology, 2000)
Human proerythroblasts and early erythroblasts, generated in vitro by normal adult progenitors, contain a pentamer protein complex comprising the tal-1 transcription factor heterodimerized with the ubiquitous E2A protein and linked to Lmo2, Ldb1, and retinoblastoma protein (pRb). The pentamer can assemble on a consensus tal-1 binding site. In the pRb(−) SAOS-2 cell line transiently transfected with a reporter plasmid containing six tal-1 binding site, pRb enhances the transcriptional activity of tal-1–E12–Lmo2 and tal-1–E12–Lmo2–Ldb1 complexes but not that of a tal-1–E12 heterodimer. We explored the functional significance of the pentamer in erythropoiesis, specifically, its transcriptional effect on the c-kit receptor, a tal-1 target gene stimulating early hematopoietic proliferation downmodulated in erythroblasts. In TF1 cells, the pentamer decreased the activity of the reporter plasmid containing the c-kit proximal promoter with two inverted E box-2 type motifs. In SAOS-2 cells the pentamer negatively regulates (i) the activity of the reporter plasmid containing the proximal human c-kit promoter and (ii) endogenous c-kit expression. In both cases pRb significantly potentiates the inhibitory effect of the tal-1–E12–Lmo2–Ldb1 tetramer. These data indicate that this pentameric complex assembled in maturing erythroblasts plays an important regulatory role in c-kit downmodulation; hypothetically, the complex may regulate the expression of other critical erythroid genes.